(untitled) (Global Journal of Medical Research, 2015)
This study investigated the haematological changes in West African Dwarf (WAD) bucks experimentally infected with Trypanosoma vivax and Trypanosoma brucei. Each of the group is eight in number while the control experimental group had five bucks. Clinical records (weight, rectal temperature) for the animals were monitored. The haematological parameters accessed include packed cell volume (PVC) estimation of Haemoglobin (HB) White and Red Blood Cell count (WBC and RBC) mean corpuscular Haemoglobin (MCH), Mean Corpuscular Haemoglobin concentration (MCHC) and were calculated accordingly.